Trends in Hospital Admissions for Sunburn in Western Australia, 1988 to 2008. (January 2013) - Duke, Janine; Wood, Fiona; Semmens, James; Edgar, Dale W.; Rea, Suzanne
The objective of this study was to assess the trends in hospitalization for sunburn in Western Australia from 1988 to 2008. De-identified linked hospital morbidity data for all index sunburn admissions in Western Australia for the period 1988 to 2008 were analyzed. Poisson regression analysis was used to estimate trends in hospital admissions. Hospitalizations increased from 1.6 (95% confidence interval [CI] = 1.0-2.2) per 100 000 person years in 1988 to 2.7 (95% CI = 1.9-3.4) per 100 000 person years in 1997, declining thereafter to 1.5 (95% CI = 1.0-2.0) per 100 000 person years in 2008. Increased hospitalizations rates were estimated for adults 25 to 44 years and 65 years or older, with a significant decline estimated for children younger than 5 years; rates remained stable for all other age groups. This study found no significant overall reduction in sunburn hospitalizations over the 20-year study period. Results raise concerns about the sun-protective behaviors and skin cancer risk of the population in Western Australia.